Exploring gaps, opportunities, barriers and enablers in malnutrition policy through key informant interviews: a qualitative inquiry from the CANDReaM initiative - Celia Laur; Heather Keller; Leah Gramlich; Carlota Basualdo-Hammond; Katherine L Ford; Roseann Nasser; Maira Quintanilha (BMJ Nutrition, Prevention & Health)
Objectives Disease-related malnutrition (DRM) presents in up to half of adults and one-third of children admitted to Canadian hospitals and significantly impacts health outcomes. Strategies to screen, diagnose and treat DRM exist but policy to facilitate implementation and sustainability are lacking. The purpose of this study was to explore gaps, opportunities, barriers and enablers for DRM policy in Canada.Methods A qualitative study was conducted with multi-national key informants in DRM and/or health policy. Purposive sampling identified participants for a semi-structured interview. The health policy triangle framework informs policy outcomes by considering actors, content, context and processes, and was used to guide this work. Inductive thematic analysis was completed, followed by deductive analysis based on the framework.Results DRM policy actors were seen as champions in healthcare, senior leaders in healthcare administration and individuals with lived experience. Policy content focused on screening, diagnosis and treatment of DRM. Key areas related to policy context included system specifics related to setting, cost and capacity, and social determinants of health. DRM policy processes were viewed as cross-sectoral and multi-level governance, mandating and other reinforcement strategies, windows of opportunity, and evaluation and research.Conclusions DRM care has advanced substantially, yet policy-level changes are sparse, and gaps exist. DRM policy is facilitated by similar content around the globe and needs to be tailored to address setting-specific needs. Actors, content, context and processes inform policy and can be a dominant lever to accelerate nutrition care best practices.